MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS 3 MI MELALUI PEMANFAATAN MEDIA PEMBELAJARAN ULAR TANGGA PINTAR - Sunarni Adelia (EL ROBIH: Jurnal Pendidikan Madrasah Ibtidaiyah, 2025)
This research was conducted with the aim of increasing the motivation to learn Mathematics of 3rd grade students of Madrasah Ibtidaiyah (MI) through the use of smart snake and ladder learning media at MI Ma'arif NU At Tijani Sokawera. This research is a Classroom Action Research (PTK) research. The results of this study show that the use of smart snake and ladder learning media can increase the motivation to learn mathematics of grade 3 students at MI Ma'arif NU At Tijani Sokawera. This can be seen from the implementation of the cycle it goes through. The first cycle saw an increase of 69%, while the second cycle increased students' motivation to learn Mathematics by 81%.